Choice of common bean segregant populations using phenotypic information and QTL microsatellite markers - Pereira, Helton Santos; Santos, João Bosco dos; Abreu, Ângela de Fátima Barbosa; Couto, Karla Rodrigues (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to select promising common bean segregant populations for grain yield and polymorphic to microsatellite markers for grain yield QTL previously identified. Fourty nine lines were utilized and evaluated in two field trials in a triple lattice. Seven lines were selected and intercrossed in a diallel scheme and genotyped with 24 single sequence repeat (SSR) markers associated to grain yield QTL previously identified. Populations were evaluated in a randomized block design with three replications. Significant differences in the general and specific combining ability were observed, and the non-additive effects were highest. The outstanding lines were RC1-10 and Z-9 due to the highest gi values. Twenty five percent of the markers were polymorphic. Four populations were chosen for selecting families based on the line evaluations, the diallel analysis and the polymorphism of SSR markers. Among the segregant populations, RC1-10 x Z-9 is remarkable for having high CEC, high grain yield of the Carioca type, and their parents expressed high CGC. Considering the low number of polymorphic microsatellite markers in each population, it is necessary to use higher number of microsatellite markers associated to grain yield QTL.